2011
DOI: 10.1016/j.homp.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Different forms of administration of biotherapy 7dH in mice experimentally infected by Trypanosoma cruzi produce different effects

Abstract: Biotherapy 7dH given before infection (7 or 30 days) produces different effects suggesting modulation of the host's immune system. The effects range from reduced parasitemia to its effective increase. The use of biotherapy to treat T. cruzi infection including dose, potency and schedule deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
6
22
0
4
Order By: Relevance
“…This result is consistent with low levels of parasitemia and provides information about the benefit of the treatment scheme used, since survival in the murine model is directly related to parasitemia levels [27]. …”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…This result is consistent with low levels of parasitemia and provides information about the benefit of the treatment scheme used, since survival in the murine model is directly related to parasitemia levels [27]. …”
Section: Resultssupporting
confidence: 73%
“…The other had negative PCR (Polymerase Chain Reaction) [24], understood as a protective action of the drug, since the treatment began at the time of the infection. Considering that the T. cruzi-Y strain shows 100% infectivity and mortality in Swiss mice [12,25-27] this result shows a patent benefit of the medication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have investigated the prophylactic and therapeutic effects of biotherapies in acute murine infection by this protozoan. These studies reported mainly parasitological, clinical, histopathological and hematological effects (Aleixo et al, 2012;Almeida et al, 2008;Ferraz et al, 2011Ferraz et al, , 2014aQueiroz et al, 2006;Sandri et al, 2015). However, only a few studies have directly investigated the immunomodulatory effects of biotherapies against T. cruzi infection (Almeida et al, 2008;Ferraz et al, 2014b;Queiroz et al, 2006;Sandri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%